Pengaruh fermentasi anaerob berbagai kotoran ternak terhadap jumlah telur larva cacing infektif dalam lumpur hasil sampingan pembuatan Gasbio - E. Harlia; Y. Astuti; D. Suryanto (Hemera Zoa, 2009)
The study on the effect of anaerobic fermentation of feces from animals (poultry, sheep and dairy cattle) on the number of eggs and infective-larvae of worms in the biogas production was conducted. The purpose of the present research is to elaborate the other benefits of biogas on the effect of environmental safety and health especially on the controlling the environment pollution by endoparasites from animal faeces. The study was conducted in the acid and neutral condition of the substrate. The result showed that the effect of anaerobic fermentation was not significantly decrease the number of infective worm-eggs (P>0,05), but significantly decrease the number of infective worm larva (P